2009
DOI: 10.1002/qua.22110
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study on (CO2)nclusters via electrostatics‐ and molecular tailoring‐based algorithm

Abstract: An algorithm based on molecular electrostatic potential (MESP) and molecular tailoring approach (MTA) for building energetically favorable molecular clusters is presented. This algorithm is tested on prototype (CO 2 ) n clusters with n ϭ 13, 20, and 25 to explore their structure, energetics, and properties. The most stable clusters in this series are seen to show more number of triangular motifs. Many-body energy decomposition analysis performed on the most stable clusters reveals that the 2-body is the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Because of the presence of methyl groups, the structures of neutral acetonitrile clusters exhibit part of the behavior of neutral methanol clusters 32,45‐51 and neutral ethanol clusters, 52‐54 which are stabilized by both hydrogen bonds and CH⋯O interactions. Besides, the dipole–dipole interactions guide the structures of acetonitrile clusters in similar arrangements as those of the carbon dioxide clusters 55‐57 and the nitrous oxide clusters 58‐60 . Oliaee et al 58 observed that the structure of the nitrous oxide tetramer has two highly symmetric isomers, one of which belonging to S 4 symmetry, similar to that of ACN4_1 found in this work.…”
Section: Resultssupporting
confidence: 78%
“…Because of the presence of methyl groups, the structures of neutral acetonitrile clusters exhibit part of the behavior of neutral methanol clusters 32,45‐51 and neutral ethanol clusters, 52‐54 which are stabilized by both hydrogen bonds and CH⋯O interactions. Besides, the dipole–dipole interactions guide the structures of acetonitrile clusters in similar arrangements as those of the carbon dioxide clusters 55‐57 and the nitrous oxide clusters 58‐60 . Oliaee et al 58 observed that the structure of the nitrous oxide tetramer has two highly symmetric isomers, one of which belonging to S 4 symmetry, similar to that of ACN4_1 found in this work.…”
Section: Resultssupporting
confidence: 78%
“…The EPIC model was also employed for predicting the structures and energetics of a large variety of weakly bonded complexes at negligible computational effort. Jovan Jose and Gadre [ 119 ] investigated the geometric patterns of (CO 2 ) n clusters, with n = 2–8, using the EPIC model for generating energetically favorable initial geometries for subsequent MP2 and DFT-based calculations. The clusters with more C=O…C interactions were found to be associated with higher stabilization energies.…”
Section: Electrostatic Potential For Intermolecular Complexation (Epic) Model and Its Applicationsmentioning
confidence: 99%
“…The larger fragment size is difficult to estimate for MTA. The estimate shown in the table is based on data in refs , , and . In MTA, the computational time scales linearly with the system size if the maximum fragment size is held fixed (which is related to the value of R g ).…”
Section: Methods and Principlesmentioning
confidence: 99%
“…Molecular clusters appear to be natural candidates for accurate treatment by fragmentation, because no covalent bonds are broken during the fragmentation process. Thus, from 2008 to the present, Gadre and co-workers have applied their MTA method to clusters of lithium dimers, CO 2 , , benzene, acetylene, , and water . Construction of such clusters and geometry optimization are facilitated by the fragmentation approach. , A fragmentation approach to the description of water clusters, in particular, has been employed by a number of authors. …”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation